Preliminary results of a multidimensional approach to screen for frailty in community-dwelling older adults of eight Italian regions: the SUNFRAIL+ study - De Luca, Vincenzo; Donnoli, Clara; Formosa, Valeria; Carnevale, Edoardo; Bisogno, Michele; Patumi, Lola; Leonardini, Lisa; Obbia, Paola; Palummeri, Ernesto; Ruatta, Manuela; Basso, Anna Maddalena; Minichini, Marcello; et al. (Frontiers in Public Health, 2025)
BackgroundFrailty syndrome in older adults is an age-related decline in many physiological systems, that results in a reduced response to minor stressors, and leading to an increased risk of falls, hospitalization, disability and death. Frailty can be prevented, reversed or mitigated by early screening for frailty risk in community-dwelling older adults, allowing for preventive interventions on clinical and social determinants.ObjectivesThe present article reports the preliminary results of the SUNFRAIL+ study multidimensional cascade assessment in a group of community-dwelling older adults of 8 Italian regions aimed to stratify the population according to the needs of care at the first administration, integrated with the quality of life (QoL) assessment to evaluate the impact of early, integrated care.MethodsThe SUNFRAIL+ study performed a multidimensional assessment of community-dwelling older adults by linking elements of the SUNFRAIL frailty assessment tool with an in-depth assessment of biopsychosocial domains of frailty, through validated questionnaires and physical tests.ResultsThe sample consisted of 743 participants (279 males and 464 females). The mean score of the multidimensional assessment with the SUNFRAIL tool was 2.31 (SD ± 0.7) with the cut-off point of frailty set at 3. The analysis revealed a significant difference in SUNFRAIL scores between the age groups. The results confirmed that individuals with higher frailty scores are significantly more likely to experience falls. Significant and conceptually valid correlations were found between physical and cognitive tests and QoL scores. Frailty is significantly associated with a lower physical and mental quality of life. The results indicated that older age and lower education levels are associated with higher frailty scores.ConclusionThe study demonstrates important different correlation levels, firstly between the assessment of frailty by SUNFRAIL and the perceived QoL; secondarily among all SUNFRAIL spheres and their second test sets that more objectively evaluate each frailty domain. The study demonstrates that the SUNFRAIL+ approach accurately assesses frailty status owing to its strong correlation with the SF-12 quality of life assessment.